IMPROVING DECISION IMPROVING DECISION MAKING IN THE EARLY PHASES OF CONFIGURATION PROJECTS - Mortensen, Niels Henrik; Harlou, Ulf; Hvam, Lars; Haug, Anders (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
During the early phases of configuration projects very important decisions are made which will heavily influence the performance of the company, benefits in different functional areas (production, sales, purchase, product development, service etc), maintenance of the configuration system and quality of the dialogue between the configuration system and the users. Today there exists very sparse tools and procedures which can assist the early phases, i.e. conceptual modeling of the products and product assortment. This paper presents a five-phase procedure for conceptual modeling in configuration projects. Each of the five phases is supported by a set of tools. The main idea of the procedure is utilization of a so-called Product Family Master Plan, which is a formal description of the product assortment and its variation. The procedure has been tested at one of Baan's (SSA Global) customers with very convincing results.